Russia Protest Against U.S. Plans to Place Military Equipment in Eastern Europe Countries in 2015 - Krisnadi, Muhammad Faiz (Universitas Muhammadiyah Yogyakarta, 2021)
After the fall of the Soviet Union thereafter the Cold War, the rivalry between the United States and Russia remains prevalent. This paper seeks to find why Russia is protesting the U.S. plan to pace military equipment in Eastern Europe. The Eastern European Region is located in the eastern part of the European continent, consisting of post-Soviet Union countries. These countries are often associated with the term